2019
DOI: 10.1016/j.psyneuen.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone administration increases social discounting in healthy males

Abstract: Although testosterone is thought to induce antisocial and aggressive behavior, research on social economic interactions has associated it with prosocial and affiliative behavior. Here, we investigated the effects of testosterone on social distance-dependent generosity in an economic discounting task where participants chose between selfish and generous alternatives. We administered testosterone gel or placebo to men in a double-blind, randomized design and measured how willing they were to share rewards with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Some such models have also examined the effects on the numerator term in the social discount model, namely, θ . For example, Wu et al (2019) showed that testosterone administration in males increased social discounting for distant others, but had no effect on generosity towards close others. Strikingly, Margittai et al (2015) showed that experimentally induced psychosocial stress appeared to have the reverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…Some such models have also examined the effects on the numerator term in the social discount model, namely, θ . For example, Wu et al (2019) showed that testosterone administration in males increased social discounting for distant others, but had no effect on generosity towards close others. Strikingly, Margittai et al (2015) showed that experimentally induced psychosocial stress appeared to have the reverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…the testosterone gel and placebo were packed identically) and purpose of the study. The donation task commenced 3 h post-dosing in accordance with previous pharmacokinetic data [22][23][24][25]. Participants also completed two additional tasks on social cognition that are not reported here.…”
Section: (B) Testosterone Administrationmentioning
confidence: 99%
“…Moreover, these results have been confirmed by more recent studies investigating the role of testosterone administration on gambling behavior. For example, males exhibited elevated impulsive and risky behavior after exogenous testosterone administration compared to the placebo group (Goudriaan et al, 2010;Van Honk et al, 2004;Van Honk et al, 2016;Wu et al, 2019;Wu et al, 2020). However, one study on male college students failed to produce the effects of testosterone using a delay discounting rate task (reflecting impulsive behaviour) (Ortner et al, 2013), possibly because of dose and gender differences (Doi et al, 2015;Wu et al, 2020).…”
Section: Testosterone and Gambling/gambling Behaviormentioning
confidence: 99%